Improving Employee Performance through Stress Management and Work-Life Balance Strategies - Soebekti, Mercyane; Kurniawati, Desi Tri (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to examine the effects of job stress and workplace environment on employee performance at the Regional Development Planning Agency of East Java, with work-life balance serving as a mediating variable.   Design/methodology/approach – A quantitative explanatory research design was employed. Data were collected through questionnaires from 110 civil servants selected using purposive sampling from a population of 285 employees. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine both direct and indirect relationships among the variables.   Findings – The results indicate that job stress has a significant effect on employee performance, whereas the workplace environment has no direct effect on performance. Work-life balance positively influences employee performance and significantly mediates the relationships between job stress, workplace environment, and employee performance. These findings underscore the importance of managing job stress and promoting work-life balance to improve employee performance in public sector organizations. The study also suggests that organizations should implement stress management initiatives and foster a supportive work environment to achieve better performance outcomes.   Originality/Value This research is original in examining work-life balance as a mediating variable between job stress, workplace environment, and employee performance in a public-sector context. The findings provide practical value by offering data-driven recommendations for policymakers to design healthier and more productive work environments.